The Behavioral Additionality of Government Research Grants - Rainer Widmann (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
There are different forms of public support for industrial R&D. Some attempt to increase innovation by prompting firms to undertake more challenging projects than they would otherwise do. Access to a dataset from one such program, the Austrian Research Promotion Agency, allows me to examine the effect of research grants on firms' patenting outcomes. My estimates suggest that a government research grant increases the propensity to file a patent application with the European Patent Office by around 12 percentage points. Stronger effects appear for more experienced firms of advanced age. Additional evidence indicates that grants induce experienced firms to develop unconventional patents and patents that draw on knowledge novel to the firm. I interpret the findings in a "exploration vs. exploitation" model, in which grants are targeted at ambitious projects that face internal competition from more conventional projects within firms. The model shows that this mechanism is more salient in experienced firms, leading to a stronger response in behavior for this group of firms.
Keywords: O38; 330